The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/foods12173263
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Edible Sesame Oil as Obtained by Green Solvents: In Silico versus Experimental Screening Approaches

Sinda Trad,
Emna Chaabani,
Wissem Aidi Wannes
et al.

Abstract: The present study aimed to investigate the qualitative and quantitative performance of five green solvents, namely 2-methyltetrahydrofuran (MeTHF), cyclopentyl methyl ether (CPME), p-cymene, d-limonene and ethanol to substitute n-hexane, for sesame seed oil extraction. In fact, both CPME and MeTHF gave higher crude yields than n-hexane (58.82, 54.91 and 50.84%, respectively). The fatty acid profile of the sesame seed oils remained constant across all the solvent systems, with a predominance of oleic acid (39.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…However, the method used to determine the UM does not consider polar unsaponifiable substances that are not soluble in petroleum ether such as phenolic compounds. Several studies have reported that 2-MeOx is also an efficient solvent for the extraction of phenolic compounds and yields polyphenol-rich extracts with high antioxidant activity. ,, In this study, the oil obtained with 2-MeOx contained a significantly higher concentration ( p < 0.05) of polyphenols than the oil obtained with hexane. The higher content of UM and phenolic compounds was probably the reason for the longer oxidative stability (induction time >70 h) compared to the hexane-extracted oil.…”
Section: Resultsmentioning
confidence: 49%
“…However, the method used to determine the UM does not consider polar unsaponifiable substances that are not soluble in petroleum ether such as phenolic compounds. Several studies have reported that 2-MeOx is also an efficient solvent for the extraction of phenolic compounds and yields polyphenol-rich extracts with high antioxidant activity. ,, In this study, the oil obtained with 2-MeOx contained a significantly higher concentration ( p < 0.05) of polyphenols than the oil obtained with hexane. The higher content of UM and phenolic compounds was probably the reason for the longer oxidative stability (induction time >70 h) compared to the hexane-extracted oil.…”
Section: Resultsmentioning
confidence: 49%
“…Sesame oil shows a highly favorable fatty acid profile, comprising approximately 80-85% unsaturated and merely 15-20% saturated fatty acids. Sesame oil primarily contains linoleic (35-50%) and oleic (35-50%) acids, alongside minor quantities of palmitic (7-12%) and stearic (3.5-6%) acids and negligible levels of linolenic acid [227,228]. Recent scientific studies have shown that an excessive intake of n-6 fatty acids might cause a physiological condition that heightens platelet aggregation and blood clotting.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%